Sago Hydrogel As Dressing For Partial Thickness Wound In Rabbits - Md Nor, Mohd Tarmizi (2001)
Brief background. At present there are various wound dressing available. Occlusive dressing is believed to promote better wound as healing compared to dry dressing. However, all the occlusive dressings available are not produced locally. In an attempt to promote our local, The Malaysian Institute of Nuclear Technology (MINT) has come out with a sago starch based occlusive dressing.